Investment in Information Technology- Students Perspective: A study in Bangladesh (Global Journal of Management and Business Research, 2018)
Education is considered as the main vehicle to eradicate poverty. Information technology (IT) facilitates education and creates global awareness. As the world become competitive, so students make them capable of competing globally, that#x2019;s why they need to access in information technology. Information Technology helps education system more students oriented. IT does not only bring change in the economic area but it also brings immense change in the education arena. In fact, IT radically changes the learning methods. Bangladesh can utilize IT facilities to create an information age. This study examines IT investment from student perspective in Bangladesh. This study also finds out usage pattern, reasons and satisfaction level of using IT from student perspective in Bangladesh. A survey is conducted on students of Bangladesh to achieve the objectives of the study. Target population answered the structured questionnaire which was developed to attain research objectives. Result shows that most of the students considered individual use are the major grounds for spending in IT, but personal and learning uses are promising reasons for IT expenditure. In IT, hardware is the key portion where students expend mostly. Moreover, students preferred foreign IT brand products while purchasing IT products.
Keywords: foreign IT brand products; global awareness; IT; information age; personal purpose